2009
DOI: 10.1074/jbc.m109.063958
|View full text |Cite
|
Sign up to set email alerts
|

NTE1-encoded Phosphatidylcholine Phospholipase B Regulates Transcription of Phospholipid Biosynthetic Genes

Abstract: The Saccharomyces cerevisiae NTE1 gene encodes an evolutionarily conserved phospholipase B localized to the endoplasmic reticulum (ER) that degrades phosphatidylcholine (PC) generating glycerophosphocholine and free fatty acids. We show here that the activity of NTE1-encoded phospholipase B (Nte1p) prevents the attenuation of transcription of genes encoding enzymes involved in phospholipid synthesis in response to increased rates of PC synthesis by affecting the nuclear localization of the transcriptional repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…More work is necessary to understand impaired derepression of phospholipid synthesis genes in orm1Δ orm2Δ cells. A recent report suggests that lipid packing within membranes can regulate derepression of phospholipid gene transcription (28).…”
Section: Discussionmentioning
confidence: 99%
“…More work is necessary to understand impaired derepression of phospholipid synthesis genes in orm1Δ orm2Δ cells. A recent report suggests that lipid packing within membranes can regulate derepression of phospholipid gene transcription (28).…”
Section: Discussionmentioning
confidence: 99%
“…The lipid regulatory transcription factor Opi1p (Greenberg et al 1982) regulates the filamentous growth MAPK pathway . The serine esterase Nte1p, which serves as the phospholipase B of yeast (Fernandez-Murray et al 2009) was also found to regulate the filamentous growth MAPK pathway ( Figure 3F). Ncr1p, which regulates sphingolipid biosynthesis (Malathi et al 2004) and has not been shown to interact with Opi1p or Nte1p genetically or physically, negatively regulated the filamentous growth MAPK pathway.…”
Section: Functional Analysis Of Candidate Genes and Pathwaysmentioning
confidence: 96%
“…As shown in Fig. 2, NTE1 encodes the serine esterase responsible for, among other things, repression of the OPI1-encoded Opi1 repressor protein (Fernández-Murray et al, 2009). The enzyme silences the yeast fatty acid synthase, helping modulate phospholipid biosynthesis in S. cerevisiae (Schweizer and Hofmann, 2004).…”
Section: In Silico Prediction Of Pathway Gene Knockouts Via Optknockmentioning
confidence: 99%